2019
DOI: 10.3390/su12010108
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Potential of Climate-Adaptive Container Building Design under Future Climates Scenarios in Three Different Climate Zones

Abstract: The deployment of containers as building modules has grown in popularity over the past years due to their inherent strength, modular construction, and relatively low cost. The upcycled container architecture is being accepted since it is more eco-friendly than using the traditional building materials with intensive carbon footprint. Moreover, owing to the unquestionable urgency of climate change, existing climate-adaptive design strategies may no longer respond effectively as they are supposed to work in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 10 publications
0
27
1
4
Order By: Relevance
“…MMC Category 1: Pre-manufacturing, 3D primary structural systems A systemized approach based on volumetric construction involving the production of three-dimensional units in controlled factory conditions before final installation. Volumetric units can be brought to the final site in a variety of forms ranging from a basic structure only to a structure with all internal and external finishes and services installed, all ready for installation T.01-Portable buildings [1,37] T.02-ISO Shipping containers [38,39] T.03-Light gauge steel modular units [40][41][42][43] T.04-Timber-framed modular units [40,42,43] T.05-CLT modular unit [40,42,43] T.06-Concrete modular units [40,43,44] MMC Category 2: Pre-manufacturing, 2D primary structural systems A systemized approach using flat-panel units used for basic floor, wall, and roof structures of varying materials which are produced in a factory environment and assembled at the final workforce to produce a final three-dimensional structure…”
Section: Category (A) [27] Prefabrication Technologies (B) References (C)mentioning
confidence: 99%
“…MMC Category 1: Pre-manufacturing, 3D primary structural systems A systemized approach based on volumetric construction involving the production of three-dimensional units in controlled factory conditions before final installation. Volumetric units can be brought to the final site in a variety of forms ranging from a basic structure only to a structure with all internal and external finishes and services installed, all ready for installation T.01-Portable buildings [1,37] T.02-ISO Shipping containers [38,39] T.03-Light gauge steel modular units [40][41][42][43] T.04-Timber-framed modular units [40,42,43] T.05-CLT modular unit [40,42,43] T.06-Concrete modular units [40,43,44] MMC Category 2: Pre-manufacturing, 2D primary structural systems A systemized approach using flat-panel units used for basic floor, wall, and roof structures of varying materials which are produced in a factory environment and assembled at the final workforce to produce a final three-dimensional structure…”
Section: Category (A) [27] Prefabrication Technologies (B) References (C)mentioning
confidence: 99%
“…This situation is getting worse as the physical features of the shipping container are made of steel. Special attention should be paid to improve both the thermal resistance and hygro-thermal capacity of the envelope due to overheating risk and more humidity issues (Shen et al, 2020). Insulation plays an important role in converting the shipping container into habitual space although Kamarazaly et al (2017) found container construction is feasible in Malaysia.…”
Section: Temperature and Relative Humiditymentioning
confidence: 99%
“…Thus, they can be one solution to the above challenges in terms of prefabricated or modular buildings. Compared to traditional building materials that have a large footprint, off-site constructed buildings are more eco-friendly and are in line with the concept of upcycled container architecture [5]. Flexible and quickly assembled modular container buildings usually consist of one or more standardized individual containers with size restrictions that depend in particular on what can be safely and economically built and transported.…”
Section: Introduction 1backgroundmentioning
confidence: 99%